Proceedings of the scientific workshop on Management and Sustainable Use of Natural Resources and Environment in Coastal Wetlands : (MERD/CRES & ACTMANG, 2000)
The workshop " Management and Sustainable Use of Natural Resources and Environment in Coastal Wetlands" is aim at gathering some study result, proposal for management of coastal resouces and urgent issues of pimary concern for the new millennium. The workshop has attracted the attention of many scientists and managers at the central level and in coastal areas,...